Quality of Public Service Government To Citizen (G2C) West Java Provincial Government Through the Sambara Application - Siti Alia; Destiani Putri Utami (Department of Public Administration, 2023)
The growth pattern of information and communication technology that is so fast encourages the government to try to implement information and communication technology in government (e-Government). In West Java, efforts to implement e-Government in public services are carried out by implementing the SAMBARA application. This application is fully oriented to make it easier for the public to access public services. However, the journey of this application was not as smooth as what had been aspired before. The implementation of this application is, in fact, not always considered good. In addition, studies regarding the SAMBARA application have not been carried out much. So that finally, the author is interested in studying this application in terms of effectiveness, efficiency, fairness, and responsiveness of services in applications that aim to measure the extent of the success of this application in terms of providing Government to Citizen (G2C) services. This study then concludes that in practice, this application is quite good, but there are also deficiencies in this application, so an improvement is needed in the future